Penerapan Asuhan Keperawatan pada Pasien Tuberkulosis Paru di RSUD Ende - Anatolia Karmelita Doondori; Yustina Paschalia; Maria Sekunda (Kelimutu Nursing Journal, 2025)
Pulmonary Tuberculosis (TB) is an infectious disease that causes the highest number of deaths in the world. Pulmonary tuberculosis is caused by the bacteria Mycobacterium Tuberculosis. Tuberculosis is a threat to the Indonesian population, because this disease is the third leading cause after heart disease and acute respiratory disease (Puspitasari et al, 2023). This case study aims to provide nursing care to Mrs. M. T with Pulmonary Tuberculosis and analyzes the gap between theory and real cases. The method used in this scientific paper is a case study method with a nursing care approach which includes assessment, nursing diagnosis, nursing intervention, implementation and nursing evaluation. The results of the case study on Mrs. M. T found the patient complaining of coughing, shortness of breath, dizziness, weakness, chest pain, cough mixed with blood, decreased appetite approximately 3 months ago, CRT>2 seconds, HGB: 2.6 mg/dL, WBC: 13.78. Nursing interventions are carried out based on nursing problems. Implementation was carried out for 3 days and the results of the evaluation were: the problem of ineffective airway clearance was partially resolved, the nutritional deficit problem was partially resolved, the peripheral perfusion problem was partially resolved and the problem of activity intolerance was resolved. Every person suffering from Pulmonary Tuberculosis has different signs and symptoms depending on how long the person has suffered and the length of treatment the patient has undergone. Therefore, it is hoped that you will maintain your health and always comply with taking medication.